E-Commerce Produk Toner Cartridge pada CV. Newton Technology Jakarta - Rafelito; Arie Kusumawati (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
E-commerce application system on the CV. Newton-based website technology is done manually with an input and confirmation system which is done in the admin and employee dashboard menus. This research aims to build an e-commerce system to expand the company's marketing and facilitate booking and rental transactions. This e-commerce application displays toner cartridge and printer rental information from CV. Newton Technology Jakarta. This system was designed using the SDLC (System Development Life Cycle) method with prototyping models and the testing technique used was black-box testing. For modeling, the UML (Unified Modeling Language) method is used, then the dabase design uses MySQL and the bootstrap interface framework, with CSS and PHP libraries.